Adverse childhood experiences and health among indigenous persons experiencing homelessness - Eric Smith; Katrina Milaney; Rita I. Henderson; Lyndon Crowshoe (BMC, 2021)
Abstract Background Current literature has established that adverse childhood experiences (ACEs) are associated with the onset of a variety of physical, mental, and behavioural illnesses. However, there are few studies that have thoroughly examined this association in low-income or marginalized groups. Methods To address this knowledge gap, this study used self-reported data on childhood experiences and adult health outcomes in a sample of 91 Indigenous persons experiencing homelessness. While the primary focus of the study was to assess the relationship between ACEs and health status, we also assessed reports on use and perceptions of health care services to test for potential illness-mitigating factors. Results Results indicated that reported number of ACEs was significantly associated with reported levels of mental illness (p < .001, d = 1.12). Significant associations were not observed for physical illness or patterns of substance use. We also found that the number of reported ACEs was significantly correlated with the number of formal health care services that an individual used (r = 0.32). Conclusions Our results reveal that the relationship between ACEs and adult illness is not as deterministic as the current literature suggests. Access to formal health care services may allow individuals to mitigate their adverse health, thereby eliminating some of the effects of ACEs. Conversely, current tools used to measure ACEs may not translate to an Indigenous population, which speaks to a need to revise ACE related surveys to include additional adversity categories.